(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2023)
The environmental analysis of the sedimentary record use different tools to characterized not just the main physical parameters of a sedimentary systems, also the development of life on it. Neoichnology, is an actualistic view of how the organisms are connected with the place where they live, providing modern models and ideas that serve as analogous. Many of the (neo)ichnological literature is concentrated on the Northern Hemisphere, and it is little known what happens southern the tropics. The description of organisms that lives either in hard- and soft-grounds is strange, and its description can help to interpret the paleodiversity in the fossil record. At Chubut province (Patagonia), in the Golfo Nuevo lives a polychaete that inhabits at the same time rocky abrasion platforms and sandy intertidal sediments. The present short-note is intended to described this occurrence and discuss its importance to ichnology.